Upaya Pemberdayaan Subak Umabun sebagai Lembaga Agribisnis di Desa Angantaka Kecamatan Abiansemal Kabupaten Badung - SUDIRA, DEWA PUTU ALIT; ASTITI, NI WAYAN SRI; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p07, 2018)
Measuring Empowerment Subak Umabun As Agribusiness Board at Village Angantaka Abiansemal Badung District Research efforts empowerment subak as agribusiness board aims to boost the economy and the welfare of farmers, so that the culture of agriculture demand and not abandoned by society, particularly Subak Umabun. This study aims to (1) identify the potential Subak Umabun related to natural resources, human resources and financial resources, (2) To know the efforts made to empower the board to Subak Umabun agribusiness. This research was conducted at Subak Umabun, the number of respondents 75 people appointed by the formula slovin, data that is used structured interviews and in-depth interviews.The results showed that the potential of Subak Umabun aspects of natural resources, human resources and financial resources are classified with an average score of 3,19. Further empowerment undertaken by Subak Umabun are classified by score of 3,21. And the last institution in agribusiness Subak Umabun high achievement score of 3,68. Based on these results, it is recommended to the government through the Department of Agriculture, Plantation and Forestry Badung need to deepen the study of this kind, so that the programs formulated by the government not only in the form of social assistance